Bergamot (Citrus bergamia): A Potential New Nutraceutical Against Cellular and Physiological Alterations Induced by Emerging Contaminants in Sentinel Organisms - Impellitteri, Federica; Multisanti, Cristiana Roberta; Riolo, Kristian; Zicarelli, Giorgia; Porretti, Miriam; Cafeo, Giovanna; Russo, Marina; Dugo, Paola; Di Bella, Giuseppa; Piccione, Giuseppe; Giannetto, Alessia; Faggio, Caterina (Antioxidants, 2025)
Nutraceuticals are gaining research interest due to their beneficial potential and their use to counter the impact of emerging contaminants on natural ecosystems. Particularly, during the COVID-19 pandemic, the use of personal hygiene/care products and disinfectants increased significantly. These products contain several substances in their formulations, including surfactants, which have proven to be hazardous to the entire aquatic ecosystem. In the present study, bergamot (Citrus bergamia) peel extract was used as a nutraceutical to counteract the toxicity of sodium lauryl sulphate (SLS), a common anionic detergent with antimicrobial activity. Specimens of Mytilus galloprovincialis, were exposed to SLS (0.01 mg/L), bergamot peels’ extract (BRG: 5 mg/L), and their mixture for 14 days. The cellular and physiological alterations in haemocytes, digestive gland (DG) and gill cells were analysed. The analyses included cell viability of haemocytes and DG cells (trypan blue exclusion assay and the neutral red retention test); the ability of DG cells to regulate their volume (RVD); haemocyte phagocytic activity; expression of genes involved in antioxidant response (Cu/ZnSOD, MnSOD, Hsp70, and CYP4Y) on gills and DG; the energy efficiency of the organism through byssus production; and the measurement of key macromolecules, including total lipid and fatty acid content, total protein, tocopherols and carotenoids, which play a key role in maintaining physiological and metabolic functions in the organism. Overall, significant differences emerged between the control (CTR) and treated groups, with the CTR and BRG groups resembling each other, while the SLS-treated groups showed significant alterations. Meanwhile, the groups exposed to the combination showed a recovery, suggesting the potential beneficial effect of the BRG.